Street Occupations, Neglected Democracy, and Contested Neoliberalism in Hong Kong - Martínez, Miguel A. (Social justice, 2019)
In the article, the author examines the history and goals of the Umbrella Movement (UM), which occupied streets in Hong Kong from September to December 2014 to call for citizens' right to universal suffrage during the election of legislators and chief executive. Also cited are the other issues raised by the protestors like poor welfare policies, increasing wealth gap, and property speculation.